Nilai-Nilai Pendidikan Karakter dalam Kitab Al-Hikam Syaikh Ibnu 'Athaillah as-Sakandari Abad ke-13 M - Mokhamad Rijal Khanif Fuadi; Ahmad Naufal Al Aziz; Moh. Sholahuddin (Getpress Management Journals, 2025)
This study aims to examine the character education values contained in Kitab Al-Hikam by Ibn ‘Athaillah as-Sakandari and to explore their integration within the context of modern Islamic schooling. The background of this research stems from the ongoing moral and spiritual crisis among students, highlighting the need for a spiritual and Sufi-based approach to character formation. Using a qualitative descriptive method through library research, this study analyzes the wisdom texts (hikmah) of Al-Hikam along with relevant literature on Islamic character education. The findings reveal that the core character values in Al-Hikam encompass three main dimensions: tauhid, which nurtures spiritual awareness and sincerity; akhlaq/ta’dzim, which instills respect, humility, and empathy; and worship (ibadah), which develops discipline and devotion in religious practice. The integration of these values can be implemented through hidden curricula, religious learning, spiritual activities, and teacher role modeling. The study concludes that Al-Hikam offers significant relevance for strengthening holistic Islamic character education aimed at fostering a generation that is faithful, knowledgeable, and morally upright.